Th estructure of personality: the return of the stratum in Philipp Lersch - Maurial Chávez, Ivan (2003)
The author explains from a reconsideration of the “deep psychology”, concept psychoanalysis and phenomenological psychology´s idea of depth which includes the contribution of the stratum theory. The protagonist of the self (spiritual soul, personal self) is emphasized as the controlling element of personality structure. The anthropological view is supported on the humanist discourse of Lopez Ibor, Victor Frankl and Leopoldo Chiappo. Likewise, personality tectonics according to Phillip Lersch is presented as an axiological integrative and plurithematic structure. Finally, the author mediates on the recovery of spirituality in psychology and on the importance of non-artificial respect for the human being as the basis of humanist psychology.